Evaluating Biophilic Architecture Patterns in Urban Parks for Enhancing Quality of Life - Agung Murti Nugroho; Jeanetta Jasmine Jandira Zipora Cayadi; Euis Elih Nurlaelih; Yuyun Qomariyah (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2025)
Urban parks shape everyday experiences in cities, especially where tourism drives local activity. This study explores how visitors interpret their well-being in relation to the biophilic design features of Batu City Square, East Java. Five quality-of-life dimensions and fourteen biophilic patterns were assessed through structured visual observations and a perception survey (n = 36), then analyzed using Importance–Performance Analysis (IPA). Field observations showed that biophilic cues appear across most spatial elements, suggesting that natural characteristics are embedded into the square’s layout rather than functioning merely as decorative additions. Physical freshness (0.27) was the strongest well-being dimension, while social intimacy (0.13) was the weakest, indicating that the square supports individual comfort more consistently than social interaction. The IPA results revealed an even distribution between attributes regarded as strengths and those considered lower priorities, reflecting visitors’ tendency to value comfort-related features more than symbolic or ecological cues.